Optical thickness identification of few-layer MoS2 deposited by chemical vapor deposition. (11th January 2019) - Zhu, Zusong; Zhu, Dequan; Zhang, Jie; Jiang, Guisheng; Yi, Mingfang; Wen, Jun
Abstract: The physical and optoelectronic properties of MoS2 are closely related to their thickness. Few-layer molybdenum disulfide (MoS2 ) has been intensively studied for its potential applications. In this work, monolayer and few-layer MoS2 nanosheets with large size and high crystallization quality were successfully prepared by chemical vapor deposition (CVD) .Then, the layer number of CVD-grown MoS2 nanosheets were identified for the first time by extracting the R channel contrast of the optical image of the sample with ImageJ software. Compared with Raman spectra and PL spectra, this method can identify the layer number of CVD-grown MoS2 nanosheets efficiently and accurately, which provides a simple and feasible method for the study of the layer number of CVD-grown MoS2 nanosheets and can help us exploiting their applications in the future.